Analisa Studi Kelayakan Sistem Informasi Penjualan pada CV. Mitra Restu Jaya Menggunakan Metode TELOS - Afilla, Dini; Saputra, Eki; Monalisa, Siti; Ahsyar, Tengku Khairil (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Manual recording of sales systems using books faces various problems that affect business efficiency and accuracy. Problems that arise include the risk of errors in recording and the difficulty of accessing data quickly and precisely. In addition, manual recording is prone to data loss or damage due to human error and physical damage to books. Therefore, the implementation of a computerized recording system is proposed. This study aims to evaluate the feasibility of implementing an information system in CV. Mitra Restu Jaya consists of four stages, namely planning, data collection, data analysis, and closing. The research consists of four stages: planning, data collection, data analysis, and conclusion. A feasibility study is used to assess whether to proceed with or halt the development of a system project, typically covering technical, economic, legal, operational, and schedule feasibility. The assessment is conducted through TELOS feasibility worksheets, containing research questions and corresponding answers rated on a scale of 6-10. Cost-benefit analysis of the information system is conducted to consider cost components and benefit components to determine project feasibility, including the calculation of the payback period (PP) and Return on Investment (ROI). The results of this study show that the TELOS method can be applied to assess the feasibility of the sales information system at CV. Mitra Restu Jaya. The assessment results for each TELOS method are 8.50 for technical feasibility, 7.50 for economic feasibility, 8.50 for legal feasibility, 7.50 for operational feasibility, and 8.50 for schedule feasibility, with an average TELOS eligibility score of about 8.10. According to the payback period calculation, the funds invested by CV. Mitra Restu Jaya can be recovered approximately 6 months after operationalization, and the sales information system is feasible because the Return-on-Investment value is around 3.33, which is greater than 1. This is supported by PIECES-framed operational feasibility proving that the system to be developed can operate effectively and efficiently in the context of a retail company. The conclusion of this research is that the sales information system is feasible to be developed at CV. Mitra Restu Jaya.